The Potential Application of The Bridging Approach In Community-Based Corrections In Indonesia: A Comparative Perspective - Hamja, Hamja; Nunna, Bhanu Prakash; Sutrisno, Endang; Sambas, Nandang; Widjajanti, Ermania (LAW REFORM, 2026)
Electronic Monitoring (EM) constitutes a sophisticated surveillance mechanism that epitomizes technological advancements within the legal sphere and acts as a feasible substitute for conventional detention practices. Nations such as South Korea have adeptly incorporated EM into a meticulously designed, community-centric training framework. Indonesia is encouraged to adopt EM; however, the effective realization of this initiative necessitates alterations to the prevailing legal and social infrastructure. This research endeavors to investigate the feasibility of EM implementation in Indonesia through a comparative analysis with the established framework in South Korea, focusing particularly on the alignment of correctional institutions, technological systems, and community engagement. Employing a comparative judicial methodology, this study assesses the legal framework, institutional arrangements, and operational procedures pertaining to EM in both jurisdictions. Findings indicate that South Korea has established a comprehensive national framework for EM, supported by centralised monitoring facilities located in Seoul and Daejeon, regional parole offices, and coordinated oversight in conjunction with law enforcement agencies. In contrast, Indonesia's correctional system remains hampered by fragmented regulatory measures, inadequate institutional collaboration, and limited technological capabilities. The lack of EM as a formally recognised legal instrument limits alternative sentencing options and exacerbates prison overcrowding. This study concludes that Indonesia requires legislative reform, capital investment in monitoring infrastructure, and enhanced inter-agency collaboration to facilitate the effective implementation of EM.